Theoretical Analysis Of Close Loop Behaviour Of Ideal Cascade Controller Structure For Positioning Of XY Table Ballscrew Drive System - Abdullah, Lokman; Jamaludin, Zamberi; Chiew, Tsung Heng; Rafan, Nur Aidawaty; Maidin, Shajahan (Trans Tech Publications, 2013)
The implementation of Classical Cascade Controller for the purpose of controlling various type of engineering appliances has been vastly utilized by control engineer community. Cascade controller provides a simple structure of controller but yet functional and have the ability to satisfy the control design requirement. In general, the controller consists of two loops, namely velocity loop and position loop. This paper is focused on the fundamental aspect on how to analyzed the close loop behaviour for both velocity and position loop and to extract the mathematical formulation of the controller. The outcome from this paper which is in the form of mathematical formula is useful and very significant in order to validate the theoretical result with the simulation result. To be more precise, the result from this research work are in the form of transfer function for both velocity and position loop of the position output, position error, dynamic stiffness of the controller and the damping ratio of the system which is in this case the XY Table Ballscrew drive system.